Treatment with paeoniflorin increases lifespan of Pseudomonas aeruginosa infected Caenorhabditis elegans by inhibiting bacterial accumulation in intestinal lumen and biofilm formation - Wang, Yuxing; Zhang, Le; Yuan, Xiaoan; Wang, Dayong (Frontiers in Pharmacology, 2023)
Paeoniflorin is one of the important components in Paeoniaceae plants. In this study, we used Caenorhabditis elegans as a model host and Pseudomonas aeruginosa as a bacterial pathogen to investigate the possible role of paeoniflorin treatment against P. aeruginosa infection in the host and the underlying mechanisms. Posttreatment with 1.25-10 mg/L paeoniflorin could significantly increase the lifespan of P. aeruginosa infected nematodes. After the infection, the P. aeruginosa colony-forming unit (CFU) and P. aeruginosa accumulation in intestinal lumen were also obviously reduced by 1.25-10 mg/L paeoniflorin treatment. The beneficial effects of paeoniflorin treatment in increasing lifespan in P. aeruginosa infected nematodes and in reducing P. aeruginosa accumulation in intestinal lumen could be inhibited by RNAi of pmk-1, egl-1, and bar-1. In addition, paeoniflorin treatment suppressed the inhibition in expressions of pmk-1, egl-1, and bar-1 caused by P. aeruginosa infection in nematodes, suggesting that paeoniflorin could increase lifespan of P. aeruginosa infected nematode by activating PMK-1, EGL-1, and BAR-1. Moreover, although treatment with 1.25-10 mg/L paeoniflorin did not show obvious anti-P. aeruginosa activity, the P. aeruginosa biofilm formation and expressions of related virulence genes (pelA, pelB, phzA, lasB, lasR, rhlA, and rhlC) were significantly inhibited by paeoniflorin treatment. Treatment with 1.25-10 mg/L paeoniflorin could further decrease the levels of related virulence factors of pyocyanin, elastase, and rhamnolipid. Therefore, paeoniflorin treatment has the potential to extend lifespan of P. aeruginosa infected hosts by reducing bacterial accumulation in intestinal lumen and inhibiting bacterial biofilm formation.